Deregulation and its discontents rewriting the rules in Asia (Edward Elgar, 2006)
Deregulation and its Discontents examines the different ways in which the issues related to deregulation and reregulation have been addressed in Asia. The role of government in business has gone through distinct, if overlapping, cycles: regulation, deregulation and reregulation. However, little is known about deregulation and even less about reregulation, particularly in relation to Asia. The contributors to this book examine the links between the cycles through detvailed analyses of the electricity market, pensions and stock markets in the Asia Pacific. They also offer an explanation of regulatory cycles